PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA DAN PEMBUATAN STEMPEL NAMA TELUR ASIN HAJAH SARNI DI DESA CERUKCUK KECAMATAN TANARA KABUPATEN SERANG - Ubay Haki; Ahnan Kasogi; Ayu Sri Lestari; Ade Irma Khoirunisa (LPPM Universitas Bina Bangsa, 2022)
The purpose of this community service is to assist in the preparation of financial reports and making stamps to individuals / small entrepreneurs, especially micro and small businesses (MSEs) in the salted egg industry center Hajah Sarni which is domiciled in Nichecuk Village, Tanara District, Serang Regency. The method of implementing this activity uses the Participatory Training method, which is to carry out activities in the form of providing counseling and assistance on how to compile simple financial reports on Hajah Sarni's micro-business as well as assistance in making salted egg name stamps. It is hoped that after the implementation of this service program, the salty egg business Hajah Sarni has the ability to compile simple financial reports, hopefully able to distinguish family finances from business finances so that business progress can be seen clearly. Furthermore, Hajah Sarni's salted egg business will also be easily recognized by consumers after her breast milk egg is affixed with a stamp with her name, finally adding creativity in the management of her industry which aims to improve her standard of living for the better